ESOP AND ORGANIZATIONAL PERFORMANCE: A CASE OF LEADING IT FIRMS (International Journal of Food and Nutritional Sciences, 2022)
interests of employees and shareholders, especially in industries like IT, where human capital is a critical asset. By offering employees ownership stakes, companies aim to enhance motivation, job satisfaction, and long-term commitment. This study explores the role of Employee Stock Ownership Plans (ESOPs) in enhancing organizational performance, specifically within leading IT firms in India. Drawing from existing literature and open-source data, the research examines how ESOPs influence key performance metrics such as Total Asset Turnover (ATO), Return on Assets (ROA), employee retention, and market perception. While the findings indicate that ESOPs may have a limited short-term effect on productivity and profitability, they play a significant role in boosting long-term employee engagement and market performance. Statistical evidence from open-source data shows that the market anticipates positive future outcomes for firms with ESOPs. However, the study underscores that ESOPs alone do not guarantee improved performance or employee motivation. Instead, their effectiveness depends on how well they align with broader organizational goals and performance strategies.